Seasonal testicular changes in Dendropsophus minutes peters, 1872 (Anura, Hylidae) - Ferreira, Adelina; Mehanna, Mahmoud [UNESP] (Inst Histol Embriol-conicet, 2012)
The reproductive cycle in anurans may be either continuous or discontinuous. These differences may be connected to seasonal climate changes and/or to anthropic activity. Forty adult male individuals of the Dendropsophus minutus species were collected during one year, in the municipality of Chapada dos Guimarães (Mato Grosso, Brazil). The testicles were studied under light and transmission electron microscopy. No variations were observed when the diameter of the seminiferous tubules and the thickness of the interstitial tissue were studied. However, changes in spermatogenesis were conspicuous and indicated that the reproductive cycle of D. minutus in Chapada dos Guimarães is discontinuous and seems related to variations in air temperature and rainfall.
Keywords: Anura; Chapada dos Guimarães; Reproduction; Spermatogenesis; Ultrastructure